2015
DOI: 10.1007/s10898-015-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

The H-differentiability and calmness of circular cone functions

Abstract: Let L θ be the circular cone in R n which includes second-order cone as a special case. For any function f from R to R, one can define a corresponding vector-valued function f L θ on R n by applying f to the spectral values of the spectral decomposition of x ∈ R n with respect to L θ . The main results of this paper are regarding the H -differentiability and calmness of circular cone function f L θ . Specifically, we investigate the relations of H -differentiability and calmness between f and f L θ . In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, generalizations of second-order cones and second-order cone complementarity sets have been examined by many authors 5,[14][15][16][17][18][19][20][21][22] . For example, authors in 14,[19][20][21][22] considered circular cones, which are generalizations of second-order cones and are, in general, nonsymmetric and non-self-dual cones. The generalized differentiability of the projection operator onto the circular cone was provided in 14,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, generalizations of second-order cones and second-order cone complementarity sets have been examined by many authors 5,[14][15][16][17][18][19][20][21][22] . For example, authors in 14,[19][20][21][22] considered circular cones, which are generalizations of second-order cones and are, in general, nonsymmetric and non-self-dual cones. The generalized differentiability of the projection operator onto the circular cone was provided in 14,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The generalized differentiability of the projection operator onto the circular cone was provided in 14,22 . Moreover, the differentiability and calmness of vectorvalued functions associated with the circular cone were also studied in 19,23 . In particular, authors in 21 showed that the results of the projection operator onto a circular cone could not be shown by simply resorting to the results of the projection operator onto the second-order cone, and hence, it is necessary to study the results of circular cone directly.…”
Section: Introductionmentioning
confidence: 99%